The Necessary Activities for the Development of Health Scientific Map in Medical Education Field: a study in Shiraz University of Medical Sciences 2011 - Mitra Amini; Mohammad Mahdi Sagheb; Javad Kojuri; Rita Rezaei; Mohammad Kazem Serajzadeh; Vahid Keshtkar; Korosh Azizi; Parisa Nabeiei (Kerman University of Medical Sciences, 2012)
Background & Objectives: Each country needs strategies and longterm plans for achieving its objectives This issue is of a great importance in our country (Iran) as the hope of all world Moslem population Twenty year vision of the Islamic Republic of Iran along with comprehensive scientific map prepared by experts in different scientific fields can help our country to achieve longterm objectives of the development The main aim of the present study was to determine sub activities of medical education fields in health scientific map from the viewpoints of experts in Shiraz University of Medical Sciences in 2011 Methods: In this qualitative study performed as focus group discussion eight faculty members of Shiraz University of Medical Sciences were selected based on their professional experience in each of the domains of comprehensive scientific map in health sector The study was performed in ten sessions in which the required activities and subactivities in each domain were determined by participants Then data were summarized classified and prioritized for each domain Results : Based on the experts viewpoints the main sub activities in each domain were as follow: Educational equity: need assessment for human resources and curriculum review Faculties: revising organizational chart and improving faculties capabilities Implementing systematic evaluation: evaluation of students and professors based on standards Improvement of students scientific level: implementing a comprehensive encouraging system and socialbased education Developing interuniversity collaboration: university independence Extending knowledge and technology boundaries: implementing evidencebased medicine in the university Quantitative and qualitative improvement of staff: modifying organizational chart of Vice Chancellor for Education Implementing clinical governance system: establishing program designing committee based on the 6item clinical governance principles Financial: improving budget chart Conclusion: Continuous programming by University managers is required to set operational planning based on the above mentioned priorities